POLSKIE PRAWO PRZEMYSŁOWE 1927-1939 - Kwiecień, Sebastian (Zeszyty Prawnicze, 2016)
POLISH INDUSTRIAL LAW 1927-1939 Summary Mutual relations between the state and industry have changed substantially in the early twentieth century. Formed the major national ompanies which have obtained legal protection acquired economic position. A manifestation of protective measures was the introduction of the concession to operate certain industrial activities. Duty concession staggered principle of freedom of industry and introduced the principle of regulation (licensing). For the period above accounted for the first codification of Polish coherent industrial such as regulation of the Polish President on 7 June 1927, industrial law, with effect from 16 December 1927, modeled primarily on the Austrian and German law on industrial property. The Act contains no provisions industry standard for the period of capitalism the first quarter of the twentieth century, and is due to the contemporary system of economic relations, which gave her more than once on the archaic nature of some regulation. In addition to the undoubted success of the enactment of uniform laws for the whole country was to move the industry with its provisions explicitly the principle of art. March 101 of the Constitution places the freedom to choose classes and earn money. A reflection of this was the provision of Article. 3 industrial law, under which the industry was to conduct free and allowed anyone, unless the provisions of industrial law did not provide that the exception or limitation. Statutory definition of industry modeled on the achievements of the jurisprudence of the German industrial law, defined it as any employment or business carried out by itself, a commercial and professional use, no matter whether it was the activities of producing, processing, trade, or services. The Act divided the industry into two basic categories: a permanent base– industry-free, fully licensed and crafts as well as no permanent residence (circular). Sometimes a third category of industries considered to run theindustry at the fair. Launch of free industry, with permanent residence, which was not subject to duty concession notice required an industrial power of the first instance. Industrial authority without undue delay seemed receipts stating the order number, under which he was entered in the register of industrial powers. The registration obligation imposed on both individuals and legal persons. Licensed industry was industry, with permanent residence, whose launch was dependent on receipt of the concession. Industrial Law provided a long list of licensed industries, while accepting the principle that only those types of industry should be forced to obtain licenses, that are thus due to the important public interest and national security had to be made subject to strict conditions. Craft was the peculiar kind of industry, with permanent residence, which could be performed only way to craft. Industry without a permanent seat was called industry is defined as a circular gainful employment, self-made, professionally and personally without a permanent seat in the industrial field, for example, selling goods in other places other than goods intended for sale. The person who wanted to lead the industry circular was required to obtain a license, which has provided industrial power of the first instance in the form of an administrative decision. It was not possible to start and perform circular industry before obtaining a license. One of the major forms of trade in the interwar period was the sale takes place at the fair. The activities fair was regulated in the law industry as a special type of industry and subject to strict legal restrictions. The basic condition of business was to obtain a fair municipality’s powers to conduct fair markets (the property or place) and keeping it in the days and hours established in the regulations. In terms of industrial law in the new political and economic conditions have occurred in Poland after 1944. It is very interesting that its provisions were not considered to be contrary to the principles of contemporary legal and political system, becoming the instrument of delivery volume of private economic activity for the so-called national economy. Therefore, the provisions of the Regulation in force until 1972.